Strategi Promosi Perpustakaan di SMA 1 IX Koto Sungai Lasi - Rahman, Ullya; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
The purpose of this paper is: (1) describe the promotion strategies undertaken by the Library of SMA Negeri 1 1X Koto Sungai Lasi, (2) describes the obstacles encountered in the promotion of State High School Library 1 1X Koto Sungai Lasi. Existing services in this paper is less effective. Descriptive method that outlines the findings or data in accordance with the activities carried out by the Library of SMA Negeri 1 Sungai Lasi 1X Koto in promotional activities. The data were obtained by interview and direct observation to employees of State High School Library 1 1X Koto Sungai Lasi. Once the data is acquired through observation and interviews subsequent to design key points in this paper.Keywords: promotion; strategies; library